A Multimodal Assignment Design to Develop Discursive Skills in Engineering - D'Silva, Faye; Tallman, Ken (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2023)
Multimodality in assignments is increasingly common in higher education, thereby requiring students to demonstrate competency in the employment of multiple modes to communicate. Specifically, the field of engineering communication relies on multimodal resources to construct meaning and convey information. This article describes the integration of multimodality in a second-year software design and communication course assignment. In this assignment, students read the text, Made to Stick that enlists six principles of effective communication strategies and are expected to apply these communicative principles to a tech talk video. Students then produce a written argument which evaluates how effectively the presenter employed Made to Stick principles. Through engagement with multimodal resources, students are afforded the opportunity to practice and develop three skills of application, analysis and argumentation.